Work-related musculoskeletal disorders and ergonomic practices among dentists in Ludhiana - R Nissi Evelyn; Ritu Jain (Wolters Kluwer Medknow Publications, 2020)
Purpose: Prolonged static postures and forceful repetitive movements predispose the dentists for musculoskeletal disorders (MSDs). The purpose of the present study was to determine the prevalence of work-related MSDs (WMSDs) among the dentists in Ludhiana, Punjab, and to assess their knowledge, attitude, and practices regarding dental ergonomics. Methodology: A questionnaire-based survey was carried out among 146 dentists in the city of Ludhiana. Results:Majority of the surveyed dental practitioners (91%) were found to be suffering from WMSDs. The most common areas affected by WMSDs in the order of magnitude were the neck (70.5%), shoulder (48.7%), lower back (47.3%), and upper back (41.8%). It was found that senior consultants had better knowledge about dental ergonomics and had a better attitude toward applying ergonomic principles in their practice. Conclusion: The high prevalence of WMSDs exists among dentists. The knowledge about dental ergonomics does not necessarily lead to a positive attitude and practice of dental ergonomics. Incorporating the teaching, monitoring, and evaluation of ergonomic principles systematically into the undergraduate and postgraduate curriculum will improve the adoption and application of these principles in the routine clinical practices.